Investigation of the Crystal Structure, Dielectric, Electrical and Microstructural Properties of Cobalt-containing Calcium Orthophosphates - Kaygili, Omer; Dorozhkin, Sergey V.; Keser, Serhat; Yakuphanoğlu, Fahrettin (Kaunas Univ Tech, 2015)
Pure hydroxyapatite and cobalt-containing calcium orthophosphate ceramics were synthesized by the sol-gel method and their properties were analyzed by Fourier transform infrared spectroscopy, X-ray diffraction, dielectric impedance spectroscopy and scanning electron microscopy techniques. The average crystallite size of the samples was found to be 30 nm - 56 nm. The crystallinity decreased gradually with the addition of Co. The resistance values were found to be similar to 10(12) Omega. Dielectric permittivity and alternating current conductivity of all the samples showed substantial changes in the presence of cobalt. The morphology and particle size distribution of all the samples were changed with increasing amount of Co. In addition, the high content of Co ions was found to both destroy the apatitic structure of the hydroxyapatite and cause the calcium deficiency. The results indicated that, in presence of high amounts of Co, Ca9.5Co(PO4)(7) ceramics could be prepared.
Keywords: ceramics; sol-gel method; X-ray diffraction (XRD); crystal structure; dielectric properties